Fusion of a 1,3-diboraruthenocene to form a slipped μ-hexahydrotetraboranaphthalene triple-decker complex with two axial C-H bonds$3hElena V. Mutseneck, Hubert Wadepohl, Markus Enders, Alexander R. Kudinov, and Walter Siebert - Mutseneck, Elena V.; Wadepohl, Hubert; Enders, Markus; Kudinov, Alexander R.; Siebert, Walter (Angewandte Chemie. International edition, 2009)
Colliding double deckers: Addition of zinc to a reaction mixture of [Cp*RuCl4]/pentamethyl-2,3-dihydro-1,3-diborole (C3B2Me5H) in THF leads to three known double- and triple-decker complexes of [C3B2Me5]−, and unexpectedly to the slipped triple-decker (see picture) with two fused diborole rings. The endo CH bonds of two MeCH groups donate two additional electrons to achieve the stable 34 VE configuration.
μ mu
First published: 30 January 2009
Gesehen am 30.11.2022